2013
DOI: 10.1007/s40262-013-0100-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetic and Pharmacodynamic Profile of Rivaroxaban

Abstract: Rivaroxaban is an oral, direct Factor Xa inhibitor that targets free and clot-bound Factor Xa and Factor Xa in the prothrombinase complex. It is absorbed rapidly, with maximum plasma concentrations being reached 2–4 h after tablet intake. Oral bioavailability is high (80–100 %) for the 10 mg tablet irrespective of food intake and for the 15 mg and 20 mg tablets when taken with food. Variability in the pharmacokinetic parameters is moderate (coefficient of variation 30–40 %). The pharmacokinetic profile of riva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
560
4
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 475 publications
(612 citation statements)
references
References 65 publications
33
560
4
15
Order By: Relevance
“…Notably, findings from our landmark analyses suggest that warfarin users initially had very good persistence, but when looking beyond the first 90 days, we found, from the cumulative incidence and the adjusted Cox model, higher persistence for apixaban and rivaroxaban and lower for dabigatran and warfarin. The fact that gastrointestinal side effects have frequently been reported in dabigatran users could potentially be a mechanism behind our finding that dabigatran users were more likely to be nonpersistent compared with apixaban users 19, 24. Several compliance studies have shown that persistence to treatment is strongly affected by the number of tablets taken daily 25.…”
Section: Discussionmentioning
confidence: 76%
“…Notably, findings from our landmark analyses suggest that warfarin users initially had very good persistence, but when looking beyond the first 90 days, we found, from the cumulative incidence and the adjusted Cox model, higher persistence for apixaban and rivaroxaban and lower for dabigatran and warfarin. The fact that gastrointestinal side effects have frequently been reported in dabigatran users could potentially be a mechanism behind our finding that dabigatran users were more likely to be nonpersistent compared with apixaban users 19, 24. Several compliance studies have shown that persistence to treatment is strongly affected by the number of tablets taken daily 25.…”
Section: Discussionmentioning
confidence: 76%
“…After multiple doses, there was no significant accumulation of the drug (Mueck et al, 2014;Kubitza et al, 2005). There are no significant differences in maximal inhibition of factor Xa activity between the first and second daily doses (Kubitza et al, 2005).…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 88%
“…This active substance presents low solubility pH-independent in water and high permeability (EMA, 2016;Mueck et al, 2014).…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations